A robust mixed‐conducting multichannel hollow fiber membrane reactor. Issue 8 (20th April 2015) - Zhu, Jiawei; Guo, Shaobin; Liu, Gongping; Liu, Zhengkun; Zhang, Zhicheng; Jin, Wanqin
<x xml:space="preserve">Abstract</x> To accelerate the commercial application of mixed‐conducting membrane reactor for catalytic reaction processes, a robust mixed‐conducting multichannel hollow fiber (MCMHF) membrane reactor was constructed and characterized in this work. The MCMHF membrane based on reduction‐tolerant and CO2‐stable SrFe0.8Nb0.2O3‐δ (SFN) oxide not only possesses a good mechanical strength but also has a high oxygen permeation flux under air/He gradient, which is about four times that of SFN disk membrane. When partial oxidation of methane (POM) was performed in the MCMHF membrane reactor, excellent reaction performance (oxygen flux of 19.2 mL min−1 cm−2, hydrogen production rate of 54.7 mL min−1 cm−2, methane conversion of 94.6% and the CO selectivity of 99%) was achieved at 1173 K. And also, the MCMHF membrane reactor for POM reaction was operated stably for 120 h without obvious degradation of reaction performance. © 2015 American Institute of Chemical Engineers AIChE J, 61: 2592–2599, 2015